The hydrolysis of 6-phosphogluconolactone in the second step of pentose phosphate pathway occurs via a two-water mechanism - Fatima, Tabeer; Rani, Sadaf; Fischer, Stefan; Efferth, Thomas; Kiani, Farooq Ahmad (Biophysical chemistry, 2018)
Hydrolysis reaction marks the basis of life yet the mechanism of this crucial biochemical reaction is not completely understood. We recently reported the mechanisms of hydrolysis of nucleoside triphosphate and phosphate monoester. These two reactions hydrolyze P-O-P and P-O-C linkages, respectively. Here, we present the mechanism of hydrolysis of δ-6-phosphogluconolactone, which is an important precursor in the second step of the pentose phosphate pathway. Its hydrolysis requires the cleavage of C-O-C linkage and its mechanism is hitherto unknown. We report three mechanisms of hydrolysis of δ-6-phosphogluconolactone based on density functional computations. In the energetically most favorable mechanism, two water molecules participate in the hydrolysis reaction and the mechanism is sequential, i.e., activation of the attacking water molecule (OH bond breaking) precedes that of the cleavage of the CO bond of the C-O-C linkage. The rate-limiting energy barrier of this mechanism is comparable to the reported experimental free energy barrier. This mechanism has similarities with the mechanism of triphosphate hydrolysis and that of hydrolytic cleavage of DNA in EcoRV enzyme. This two-water sequential hydrolysis mechanism could be the unified mechanism required for the hydrolysis of other hydrolysable species in living cells.
Gesehen am 23.04.2020